1985
DOI: 10.1128/mcb.5.4.734
|View full text |Cite
|
Sign up to set email alerts
|

UV stimulation of DNA-mediated transformation of human cells.

Abstract: Irradiation of dominant marker DNA with UV light (150 to 1,000 J/m4) was found to stimulate the transformation of human cells by this marker from two-to more than fourfold. This phenomenon is also displayed by xeroderma pigmentosum cells (complementation groups A and F), which are deficient in the excision repair of UV-induced pyrimidine dimers in the DNA. Also, exposure to UV of the transfected (xeroderma pigmentosum) cells enhanced the transfection efficiency. Removal of the pyrimidine dimers from the DNA by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 36 publications
4
11
1
Order By: Relevance
“…No UV-dependent enhancement of plasmid-chromosome recombination was observed, in contrast to reports that homologous interviral recombination (13), homologous intrachromosomal recombination (72), and nonhomologous plasmid integration (43,59,65) were enhanced by UV irradiation. Gamma irradiation and double-strand breaks enhanced pSV3neo-Ap-recombination, so the observation that UV light increased the frequency of mutant (mostly degraded) plasmids almost 10-fold but did not affect recombination was a bit contradictory.…”
Section: Discussioncontrasting
confidence: 49%
“…No UV-dependent enhancement of plasmid-chromosome recombination was observed, in contrast to reports that homologous interviral recombination (13), homologous intrachromosomal recombination (72), and nonhomologous plasmid integration (43,59,65) were enhanced by UV irradiation. Gamma irradiation and double-strand breaks enhanced pSV3neo-Ap-recombination, so the observation that UV light increased the frequency of mutant (mostly degraded) plasmids almost 10-fold but did not affect recombination was a bit contradictory.…”
Section: Discussioncontrasting
confidence: 49%
“…We and others have demonstrated that cyclobutane pyrimidine dimers are predominantly responsible for shortwavelength UV-enhanced transformation (36,42), whereas DNA lesions such as thymine glycols or apurinic sites do not induce the phenomenon (36). Stimulation of transformation with UV-induced pyrimidine dimers and with psoralen adducts both involve lesions in cyclobutane rings on pyrimidine bases.…”
Section: Discussionmentioning
confidence: 99%
“…As a model system to study chromosomal rearrangements, we are using integration of plasmid DNA into mammalian chromosomes. We and others have demonstrated that UV irradiation of pSV2-derived shuttle vectors enhances the potential of the vectors to transform human cells (35,42). Integration of the vector DNA into host chromosomes appears to occur through nonhomologous recombination (20,34,37,39).…”
mentioning
confidence: 99%
“…To date, the use of defective human cell lines such as XP, Fanconi's anemia, and ataxia telangiectasia in transformation experiments with genomic DNAs has been unsuccessful (20). This is due, at least in part, to the reduced amounts of stably integrated DNA in human lines relative to many rodent lines (14,47). Some success with correction of XP cells has been achieved by fusion of X-ray-inactivated CHO cells with XP group A (17), resulting in primary hybrids having -2% hamster DNA.…”
mentioning
confidence: 99%